Digital revolution: Capital and Sales on the Profitability Ratio of MSMEs in Majene - Futri Ayu Wulandari; Nanda Ariyandani; Wulan Ayuandiani (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2024)
Companies seek to maximize performance to retain new investors Existing investors want to increase investment in working capital and current fortunes. Profit is an important goal for companies to grow Business growth. This study focuses on the financial performance of MSMEs (Micro, Small, and Medium Enterprises) in the Majene Regency area, specifically looking at working capital and sales volume. A quantitative approach using a descriptive methodology was the research methodology employed. The study collected data from 30 MSMEs through a Roscoe technique. The data was then analyzed using multiple regression statistical tests. According to the findings, when taken into account jointly, working capital and sales volume significantly and favorably impact profitability. However, when considered individually, the increase in working capital was found to have an insignificant positive impact on profitability, while the increase in sales volume was found to have a positive and significant effect. In order to increase firm profitability, the report recommends that MSMEs in the Majene Regency concentrate on growing sales volume and making the most use of working capital.